SURVEY KEPUASAN MASYARAKAT TERHADAP PELAYANAN E-KTP DI KECAMATAN TEMBALANG KOTA SEMARANG - Ratri Nur Kholifah; Budi Setiyono (Journal of Politic and Government Studies, 2019)
In this study aims to determine the level of satisfaction of the community in Tembalang District to the services provided in Tembalang District specifically in serving the making of E-KTP through IKM Conversion Value which refers to the Regulation of the Minister of Administrative Reform and Bureaucratic Reform Number 14 of 2017 concerning Guidelines for Preparation of Satisfaction Survey Public Service Provider Unit.This study uses quantitative methods. The sampling technique used in this study is non-probability sampling technique with incidental sampling type using data from observations, documentation, and questionnaires.The results showed that the value of the Community Satisfaction Index (IKM) service for making E-KTP in the Population and Civil Registration Service of Tembalang District, Semarang City was 80.85 with a weighted average value of 3.2. Then the level of satisfaction of the people in Tembalang District, Semarang City is in the Satisfied category. The results of the calculation of the 9 elements of the Community Satisfaction Index (IKM) are as follows: (1) Service Requirements which have IKM convergence values of 81,31 in the Satisfied category, (2) Service Procedures which have a IKM convergence value of 81,31 with the Satisfied category, ( 3) Service Time which has an IKM convergence value of 77,47in the Satisfied category, (4) Service Cost / Tariff which has IKM convergence value of 84,34 with the Satisfied category, (5) Service Product which has a IKM convergence value of 81.04with the Satisfied category, (6) Service Implementing Competencies which have a IKM convergence score of 76,64in the Satisfied category, (7) Service Implementing Behavior which has an IKM converging value of 82,4 in the Satisfied category, (8) Handling complaints, suggestions, and input handling complaints, suggestions, and input 76.64 with the category of Satisfied (9) Service Facilities and Infrastructure which has a IKM convergence value of 86,53 with the Satisfied category.Thus community satisfaction is related to the level of one's feelings after comparing the perceived performance / results with their expectations. If the community is not satisfied, this indicates that the performance carried out by the service provider. To achieve progress, service providers must recognize the importance of increasing work productivity and if the service is good, service providers must maintain performance and continue to increase productivity so that the community remains or more satisfied with the services provided. In this study the service provider for making E-KTP in the TPDK of the Population and Civil Registration Service of Tembalang District, Semarang City, must maintain performance productivity and must improve the quality of performance.